Analysis of the Effect of Wastewater Quality on the Effectiveness of Eco-Enzyme - Viareco, Hariestya; Yanova, Shally; Jalius, Jalius; Naswir, Muhammad; Dewi, Nabila Sastra; Mutmainnah, Elma; Ziadah, Besse Syaharani; Khatamsi, Muhammad; Putri, Prameswari Amalia; Zahra, Kintan Larasati; Wahyuni, Dini Sri; Meduripa, Harry Fajra; Iskandar, Jumary (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
Eco-enzyme represents a biological solution derived from the fermentation of organic materials, evaluated for its effectiveness in industrial wastewater treatment. This study examines to investigate the effectiveness of eco-enzymes in improving the quality of industrial wastewater by analyzing their impact on four specific types of liquid waste: landfill leachate, tofu wastewater, batik wastewater, and laundry wastewater. Samples were treated with eco-enzyme at specific concentrations and incubated for 5 days, followed by chemical analysis. Eco-enzyme reduced ammonia levels in landfill leachate by 57% to 8.83 mg/L, though COD and BOD values rose to 18,114.6 mg/L and 46,709 mg/L, respectively, exceeding effluent standards. In tofu wastewater, COD and BOD decreased by 72% and 75% to 4,189.68 mg/L and 2,395.3 mg/L, respectively, but remained above regulatory limits. Batik wastewater showed increases in most parameters, with COD and BOD reaching 6,838.85 mg/L and 3,193.5 mg/L. For laundry wastewater, surfactants decreased by 55% to 12.97 mg/L, but BOD and TSS increased. These findings indicate that while eco-enzyme can reduce specific pollutants like ammonia and surfactants, its application can also elevate COD and BOD levels in some cases. Additional treatment processes, such as aeration or coagulation, are required to achieve effluent standards. Despite its limitations, eco-enzyme holds potential as an environmentally friendly option for industrial wastewater management when integrated with complementary technologies.